Vector control Aedes sp. during pandemic COVID-19 - Nur Alvira; Eka Silvia Saputri; Fajarina Lathu Asmarani; Rizky Erwanto; Venny Vidayanti (International Journal of Public Health Science (IJPHS), 2021)
During the coronavirus disease 2019 (COVID-19) outbreak in Indonesia, the government also faces another health problem, namely dengue hemorrhagic fever (DHF). The routine activities of the dengue management system have been significantly curtailed as government authorities concentrate more on containing the transmission of the COVID-19. This study aimed to describe vector control Aedes sp. during pandemic COVID-19, such as community activities in controlling breeding places, area risk, vector density and the determinant factors. This study was a community-based cross-sectional survey involving 136 households in the endemic area of Gondokusuman District, Yogyakarta, Indonesia using proportionate stratified random sampling. Data analysis was performed through simple and multiple logistic regression tests. Vector control for Aedes sp. breeding places during pandemic COVID-19 in the community are still low; the high level of vector density proves this based on House Index (HI): 44.1%, container index (CI): 57.4%, and Breteau Index (BI): 213.2%. This district is also at high risk to be the breeding places of Aedes sp. based on maya index (MI): 64.7%. The determinant factor that affects this condition is the lack of support by health workers/cadres during the COVID-19 pandemic.